Kepemimpinan Transformasional Yesus sebagai Model Kepemimpinan Toleran di Indonesia - Seran, Juliati Elisabeth (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
The role of leadership in a religion is particularly important in building an attitude of altruism in the people it leads. However, what is currently a problem is the intolerant attitude of religious leaders which has an impact on the emergence of intolerant attitudes within the people they lead. Because of these problems, this article was written with the aim of looking at the ideal attitudes and behavior that religious leaders should have in relation to relations between religious communities. This article can be a contribution for leaders to have an attitude of altruism in order to build harmonious relations between religious communities. In achieving this goal, the author uses qualitative research methods using literature study. The results of this research are that the attitudes of religious leaders must be reflected in transformational leadership such as the leadership of Jesus where universal love was the basis of His leadership, which ultimately brought changes to His followers specifically in establishing life relationships with others.